Learning in Noisy Classrooms: Children's Reports of Annoyance and Distraction from Noise are Associated with Individual Differences in Mind-Wandering and Switching skills. Issue 1 (January 2022) - Massonnié, Jessica; Frasseto, Philippe; Mareschal, Denis; Kirkham, Natasha Z.
Classrooms are noisy, yet little is known about pupils' subjective reactions to noise. We surveyed 112 children between 8.70 and 11.38 years of age and extracted five dimensions in their reactions to noise by factorial analyses: (1) perceived classroom loudness, (2) hearing difficulties, (3) attention capture, (4) interference, (5) annoyance from noise. Structural Equation Models were run to better understand interindividual differences in noise interference and annoyance. Children reporting hearing and switching difficulties experienced more interference and annoyance from noise. Children who had a greater propensity for mind-wandering also experienced more interference from noise, but were annoyed by noise only to the extent that it produced interference—the relationship between mind-wandering and noise annoyance was indirect, and not direct, as was the case for reported hearing and switching difficulties. We suggest that the distinction between annoyance and interference has theoretical, empirical, and practical relevance for educational research.